Predicting Consumer Purchase Intention in Personal Shopper Services Using Big Data Analytics and SEM - Suryari Purnama; Cicilia Sriliasta Bangun; Erlina Puspitaloka Mahadewi (International Institute for Advanced Science & Technology (IIAST), 2025)
The rapid growth of informal personal shopper (Jastip) services in Indonesia, driven by social media, reflects a growing market demand for convenient access to diverse products, though the lack of formal guarantees in transactions highlights the critical role of consumer trust. This study aims to explore the antecedents of consumer trust price, perceived risk, and reputation and their influence on online purchase intention within the Jastip context. Employing a quantitative research approach with a causal design, data was collected from 130 Jastip consumers in Jakarta, Indonesia, via an online questionnaire, and analyzed using Structural Equation Modeling (SEM) with Lisrel software. The results indicate that price and reputation significantly and positively influence consumer trust, which in turn directly impacts online purchase intention. Crucially, consumer trust fully mediates the relationship between price and online purchase intention, as well as between reputation and online purchase intention. However, perceived risk was found to have no significant influence on consumer trust, nor did it mediate the relationship between perceived risk and online purchase intention. These findings highlight the importance of price perception and reputation in cultivating consumer trust, which is essential for driving online purchase intention in Jastip services, while suggesting that factors like hedonic motivations or social trust may override traditional risk assessments in informal online service contexts.